Acesso e integralidade na saúde bucal no Brasil: análise a partir dos dados do Programa Nacional de Melhoria do Acesso e da Qualidade da Atenção Básica (PMAQ-AB) - Pezzini, Muriel Stein (2021)
The present study, which is of quantitative approach, seeks to analyze the evolution of oral health within Brazil’s Primary Health Care, regarding the access to services and the integrality of attention based on data from the National Program for Access and Quality Improvement in Primary Care (PMAQ-AB). The program was implemented in 2011 and consists of a proposal for changes in the functioning and offer of Primary Care, with the aim of upgrading health services accessibility and the quality of them. Three cycles have been concluded up to this moment, which took place in the years 2011-2012, 2013-2014 and 2015-2018, respectively. One of the phases of the program is the external evaluation, in which health professionals and users answer a questionnaire related to the work process of reference teams. In order to make a valid comparison, questions from the external evaluation were selected and formulated in the same way in different cycles of the program, producing a total of 18. In relation to access, the insertion of Oral Health Teams was analyzed based on the total number of participating teams in the three cycles, and three variables from the first and third cycles answered by the users were selected. With regard to integrality, 14 variables were selected from the program’s three cycles, which were answered by oral health professionals. The access sample was composed of 17.202 teams in the first cycle; 29.778 in the second; and 37.350 in the third one; and of 46.362 users of the first cycle and 62.161 of the third one. The integrality sample was composed of 12.403 Oral Health Teams in the first cycle, 18.364 in the second cycle and 22.993 in the third one. Data were collected on the website of the Ministry of Health, grouped by region, presented in the form of tables graphs and analyzed according to Chi-square and Marascuilo Tests. Among the results, there was a reduction in the proportion of teams with oral health in the country from 72.1% to 61.7% and 61.6%, with the highest values in the Northeast (85.5%) and Central-West regions (83.4%) in the first cycle; and growth in scheduling a first appointment from 56,0% to 92,0%. High attendance to spontaneous demand, with values above 96,0% in the third cycle in all regions. The existence of specialized care was less than 71,0% in all regions in the last cycle and the stomatology reference showed the highest growth rates, 18,0% in Brazil. It is concluded that there were changes in the profile of dental services in Primary Care and that the socioeconomic characteristics, the work process and the healthcare model of each region are reflected in the coverage, quality and usage of dental services. The regions where Family Health Strategy is applied more intensely display more favorable results when it comes to oral health care.